Dampahinga a coconut development and farm resort complex in Marinduque - Labay, Francine Mae L.; Alex Ray P. Evangelista (Quezon City College of Architecture, University of the Philippines Diliman, 2025)
Agriculture and tourism are pivotal sectors that drive employment and economic growth
in the Philippines. Agritourism integrates these industries to enhance rural quality of
life and boost local economies through sustainable agricultural practices. Despite its
significance, this sector is still underutilized in the local context. Marinduque, an island
rich in culture and natural resources, remains largely unexplored. Its abundance in
coconut presents an opportunity that can be leveraged for ventures that would provide
additional income for local farmers. This comprehensive design project seeks to boost
the agritourism potential of Marinduque by employing architectural strategies that
creates a balance between development and environmental conservation through a farm
resort complex. Guided by the principles of experiential architecture, the design product
translates qualitative analyses into a tangible facility that streamlines the coconut
farming processes in Marinduque, while crafting an engaging and immersive experience
for its prospective tourists.
Include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Agritourism -- Marinduque; Coconut farming -- Marinduque; Resort architecture -- Marinduque